Dialogues on distribution of powers and responsibilities in federal countries - Blindenbacher, Raoul; Ostien, Abigail, 1971- (Global dialogue on federalism booklet series, 2005)
These lively, timely, and accessible dialogues on federal systems provide a comparative snapshot of each topic and include comparative analyses, glossaries of country-specific terminology, and a timeline of major constitutional events. Countries considered include Argentina, Australia, Austria, Belgium, Brazil, Canada, Germany, India, Mexico, Nigeria, Russia, South Africa, Spain, Switzerland, and the United States. Whether you are a student or teacher of federalism, working in the field of federalism, or simply interested in the topic, these booklets will prove to be an insightful, brief exploration of the topic at hand in each of the featured countries. Contributors include Sarah Byrne (Université de Fribourg), Marcelo Piancastelli de Siqueira (Institute for Applied Economic Research, Brasillia), Hugues Dumont (Facultés Universitaires Saint-Louis, Brussels), J.Isawa Elaigwu (Institute of Governance and Social Research, Jos), Thomas Fleiner (Université de Fribourg), Xavier Bernadi Gil (Universitat Pompeu Fabra, Barcelona), Ellis Katz (International Association of Centers for Federal Studies, PA), Nicolas Lagasse (Facultés Universitaires Saint-Louis, Brussels), Clement Macintyre (University of Adelaide), George Mathew (Institute of Social Sciences, New Delhi), Manuel González Oropeza (Universidad Nacional Autónoma de México), Hans-Peter Schneider (Universität Hannover), Richard Simeon (University of Toronto), Clara Velasco (Universitat Pompeu Fabra, Barcelona), Ronald L. Watts (Queen's University), and John Williams (Australian National University, Canberra).